Frequency of Life Events Among Patients With Panic Disorder Presenting to Psychiatric OPD - Hameed, Abdul; Khan, Hazrat Ali; Anwar, Mohammad; Ain, Qurat ul; Khan, Khushhal; Naseem, Muhammed; Muhammad, Shah; Ullah, Naseeb; Kakar, Sana Ullah (Biological and Clinical Sciences Research Journal, 2025)
A persistent and crippling mental illness, panic disorder (PD) is frequently brought on by or made worse by stressful life events (SLEs). There is little study from low- and middle-income nations like Pakistan, despite the fact that studies conducted worldwide have linked life stressors to Parkinson's disease. The kind and frequency of life events linked to Parkinson's disease may be influenced by the distinct sociocultural and economic environment of places like Quetta. Objectives: Assessing the frequency and kind of stressful life events among patients with panic disorder who present to a psychiatric outpatient department (OPD) was the main goal of this study. Assessing the temporal correlation between these occurrences and the start or worsening of panic symptoms was a secondary goal. Methods: In this qualitative study, 150 patients, ages 18 to 60, who were admitted to the psychiatric outpatient department of a Quetta tertiary care hospital and had been diagnosed with panic disorder according to DSM-5 criteria. Semi-structured interviews based on a modified version of the Life Events and Difficulties Schedule (LEDS) were carried out using purposive random sampling. Transcribed interviews were subjected to thematic analysis in order to find recurrent themes in the pressures in life and how these stressors were thought to affect panic symptoms. Results: Sixty-eight percent of participants were married, and 56 percent were women. Marital or relationship troubles (41.3%), the loss of a close relative (37.3%), serious health problems (31.3%), and stress linked to money or work (27.3%) were the most often reported life events in the previous year. Most (74.7%) said they had gone through important life events in the three months before they started having symptoms. 32% said the event had a slight or moderate effect on their panic symptoms, whereas more than half (55.3%) thought it was a severe trigger. Conclusion: The study demonstrates a robust psychological and temporal association between stressful life experiences and the development or exacerbation of symptoms associated with panic disorder. The biggest contributors were financial stress, bereavement, and marital discord. In order to improve treatment results for panic disorder, our findings highlight the necessity of regular psychosocial assessment, culturally specific therapies, and larger socioeconomic support networks.